Modeling causes of cost overrun in large construction projects with partial least square-SEM approach: contractor's perspective - Abdul Rahman, Ismail (Maxwell Scientific Organization, 2013)
Construction cost overrun is a major problem faced by the construction industry globally and it needs serious attention to alleviate. Cost overrun is a result of one or combination of several causes which are very important to identify for effective cost performance. Current methodologies focusing on the identification of causes does not give the insight of underlying relationships between the causes. Hence, this study focused on studying the fundamental relationship between factors of cost overrun using Partial Least Square-SEM method. This is an advanced multivariate analysis technique for estimating and analyzing causal relationships in path models. Data collection was carried out with structured questionnaire survey amongst contractors involving in large construction projects in Malaysia. Hierarchal model for assessing causative factors and cost overrun was developed and analyzed using Smart PLS software of SEM and it was found that contractor's site management related factors had strong effect on cost overrun. The calculated Global Fit (GoF) Index of model was 0.405, which indicates that the developed model had substantial explaining power to represent the Malaysia construction industry focused of large construction projects. Hence, improvement in contractor's site management is the critical requirement to control construction cost overrun. Keywords: Construction